HBR Case Studies: Keeping Strategy on Track - Authors (Harvard Business Press, 2004)
Few management topics generate as much discussion--and disagreement--as strategy. Should you grow from the core, or expand into new markets? Do you really need take your company global? Should you make that next acquisition, or are you "growing for broke?"